UPAYA COMIC RELIEF DALAM MENINGKATKAN KESEHATAN DI GHANA TAHUN 2013 - Aulia Faradipta Hakma; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is a contemporary study which explain the efforts from a non-governmental international organization that operates as a charity foundation called Comic Relie f to improving healthiness in Ghana at 2013. Comic Relief was established initially in Britain in 1988 by the English-born New Zealand scriptwriter Richard Curtis and Alexander Mendis in response to the famine in Ethiopia. After that, Comic Relief becomes a charity that stands with a vision of the world to be just, free from poverty and with a mission to encourage positive change through the power of entertainment.This is qualitative research which used descriptive methods, and collecting datas from some resources like books,journals, official publications and relevant websites. This paper used the pluralism perspective and International Organizations written by Clive Archer. The object in this research is Comic Relief as an main actor in International Relations.The result of this research shows that Comic Relief creates some programs and efforts that involving several parties such as international organizations, corporations, UK Government, medias, and public figures in social aspect. The programs and efforts such as making television programs, visiting marginalized country to get to know how to help them and donate the funds to the British and African countries.Key words : Comic Relief, Red Nose Day, Sport Relief